Species-group concepts and biogeography of the genus Crotonia (Acari: Oribatida: Crotoniidae), with new species from South and Central America - Colloff, Matthew J. (Zootaxa, 2009)
Five new species of oribatid mite belonging to the Gondwanan genus Crotonia are described from South and Central America: C. macfadyeni sp. nov. from the Falkland Islands, C. carioca sp. nov. from Brazil, C. valdivia sp. nov. and C. wallworki sp. nov. both from Chile, and C. aculeata sp. nov. from Guatemala. The nymphal stages of C. macfadyeni are also described. The species-groups of Crotonia delineated by Luxton (1982) are redefined in relation to these new species and a re-evaluation of characters. Previously, the primary character for defining species-groups was the arrangement of the caudal apophyses. Greater emphasis is placed herein on the fusion of the dorsal shield with the rest of the notogaster and the presence or absence of a lateral hyaline region. The Nukuhivae group is merged into the Unguifera group (containing C. carioca sp. nov., C. cervicornia, C. melanesiae, C. nukuhivae and C. unguifera) and the Caudalis group into the Obtecta group (containing C. blaszaki, C. obtecta, C. pulchra, C. caudalis, C. cupulata, C. longibulba and C. tuberculata). The biogeography of Crotonia is re-assessed based on 43 recognised species. The redefined Obtecta group has a disjunct trans-Pacific distribution. The Unguifera group, present in the Neotropics, is also found in an arc from New Zealand to the Philippines and has also dispersed to the mid-Pacific Marquesas Islands. Three new speciesgroups are established. The Flagellata group, containing C. flagellata and C. reticulata, also has a disjunct trans-Pacific distribution. The Lanceolata group is dominated by species from oceanic islands and contains C. brassicae, C. lanceolata and C. perforata from St. Helena, C. brevicornuta from Campbell Island, and C. ovata from Tasmania. The Capistrata group contains those species which possess the full complement of setae in the c series (C. alluaudi, C. americana, C. ardala, C. borbora, C. capistrata, C. dicella, C. ecphyla, C. pauropelor, C. tasmaniana and C. tryjanowskii). It has a disjunct continental distribution represented in the Neotropical, Afrotropical and Australasian regions. The Cophinaria group (C. aculeata sp. nov., C. brachyrostrum, C. chiloensis, C. cophinaria, C. jethurmerae, C. lyrata, C. macfadyeni sp. nov., C. marlenae, C. pyemaireneri, C. ramus, C. rothschildi, C. valdivia sp. nov. and C. wallworki sp. nov.) has a similar distribution to the Capistrata group. The Afrotropical region has lowest diversity (two species-groups, six